028 How Do Clinicians Like and Understand Trustworthy Guidelines? Randomised Controlled Trial Using Clickers in Educational Sessions. (15th August 2013) - Vandvik, P; Brandt, L; Kristiansen, A; Alonso, P; Agoritsas, T; Akl, E; Guyatt, G
Abstract : Background: Clinical practice guidelines (CPG) often have shortcomings in presentation formats that limit dissemination at the point of care. As part of the DECIDE project we have developed multilayered CPG presentation formats. Comprehensive user-testing of the formats has provided us with alternative presentation formats now ready for randomised trials but also an important insight: Insufficient conceptual understanding of guideline methodology (e.g. strength of recommendations and quality of evidence) may hamper application of CPG recommendations in practice. Objectives: To determine physicians' understanding, attitudes and preferences concerning trustworthy guidelines in traditional and new presentation formats (DECIDE A and B). Methods: In this randomised controlled trial we will recruit 100 physicians attending a standardised lecture with 3 components: 1) presentation of clinical scenario, 2) explanations of key concepts of trustworthy CPG (e.g. GRADE, AGREE II) and 3) presentation of a current trustworthy CPG relevant to the scenario, displayed in traditional PDF format and DECIDE A and B formats. Throughout the lecture participants will answer questions with 'Clickers' and be randomly assigned to alternative presentation formats by concealed allocation and blinding, through the use of eyepatches. Results: We will present results from the trial at the conference. Discussion: If our approach of integrating randomised trials into educational sessions is feasible and provides valid results we will conduct multiple such trials in DECIDE. Implications for Guideline Developers and Users: Optimised GL presentation formats and sufficient conceptual understanding, as researched in this trial, should facilitate the uptake of trustworthy CPG and application of research evidence in practice.